Sociolingvistinė situacija šiaurės Rytų Lietuvoje tarpukario anketų duomenimis - Sinkevičiūtė, Daiva (Baltistica, 2006)
THE SOCIOLINGUISTIC SITUATION IN NORTHEASTERN LITHUANIA AS SHOWN BY QUESTIONNAIRES OF THE INTERWAR PERIOD The interwar period questionnaires composed to investigate Northeastern Lithuanian spoken language also contain particular information about the social situation of the rural areas. The 1933–1935 questionnaires made by Antanas Valaitis show that Lithuanian was the main language spoken in the villages visited by the investigator. The non-Lithuanian speaking villages were sporadic. The village inhabitants usually prayed in the same language they spoke at home. There were only rare instances when the elderly inhabitants prayed in Polish, explaining they had been forced to do so by their Polish landlords. Among the rural districts investigated by Valaitis, the largest number of literate inhabitants was found in the Tverečius district, and the most active social organization in Northeastern Lithuania was the Society of St. Casimirus.